Doing Research in the Real World - David E. Gray (USA Sage, 2022)
From first planning to writing up your research, this complete guide will help you push your project forward. Walking you through every step you need to take, it helps you build your knowledge of theory and methods and offers straightforward guidance to empower you to make good research decisions and learn best practice. This fifth edition: Draws on over 70 case studies of research in action to demonstrate potential pitfalls - and how to avoid them. Adds a new chapter on data management, providing how-to guidance on storing your research data. Provides more than 150 activities to help you develop your understanding of key concepts and advance your research methods knowledge. Illustrates how research methods skills transfer to the workplace, helping you boost your employability. Accompanied by online resources including videos, case studies and further reading that bring methods to life, this accessible book is still the definitive research companion for any student doing a research project.
Keywords: Research; Research methods; Textbooks; Research Methods (BIN2044-N)